2020
DOI: 10.7120/09627286.29.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Validation of histological and visual scoring systems for foot-pad dermatitis in broiler chickens

Abstract: In this study, an appropriate visual scoring system for foot-pad dermatitis was validated, considering the histologically measured depth of the inflammation zone and the histopathological grade (no lesion, mild lesion, ulcer). The aim being to evaluate whether the visual, macroscopic scoring of foot-pad dermatitis can represent the histological, microscopic findings. Two hundred Ross 308 broiler chicken feet (birds aged 39–42 fattening days) were collected at a slaughterhouse and scored macroscopically accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…According to a study by Stracke et al ( 14 ), there is a link between the occurrence of ulcerations and the size of the lesion on the metatarsal pad, findings which are in agreement with Toppel et al ( 13 ). Similar results were observed for broiler chickens ( 19 , 20 ). However, using the standard scoring system of Hocking et al ( 11 ), the study by Stracke et al ( 14 ) also showed that no differences in severity of ulcerations were found between the higher scoring levels (scoring levels 2, 3, and 4).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…According to a study by Stracke et al ( 14 ), there is a link between the occurrence of ulcerations and the size of the lesion on the metatarsal pad, findings which are in agreement with Toppel et al ( 13 ). Similar results were observed for broiler chickens ( 19 , 20 ). However, using the standard scoring system of Hocking et al ( 11 ), the study by Stracke et al ( 14 ) also showed that no differences in severity of ulcerations were found between the higher scoring levels (scoring levels 2, 3, and 4).…”
Section: Introductionsupporting
confidence: 87%
“…Even if included in some of the studies evaluating FPD in turkeys ( 1 ) and in assessment schemes in Germany ( 6 ), the digital pads are currently not included in the evaluation when using standard scoring systems for practical applications ( 9 , 11 ). In contrast to turkeys, scoring systems used in broilers partially include lesions on the digital pads ( 20 ) though only in the highest severity grades. According to the literature ( 11 , 21 , 22 ), the assumption was that with rising severity grades of altered lesions on the metatarsal pad, alterations on digital pads would increase alike.…”
Section: Discussionmentioning
confidence: 99%
“…They vary in the number of score categories and the approach of the assessment. In most of the scoring systems, three [10][11][12], four [13,14] or five [15][16][17] categories are used for the classification of FPD. In some systems, especially the size of the FPD, lesions are considered [16], whereas other systems consider the depth or severity of FPD [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In most of the scoring systems, three [10][11][12], four [13,14] or five [15][16][17] categories are used for the classification of FPD. In some systems, especially the size of the FPD, lesions are considered [16], whereas other systems consider the depth or severity of FPD [13,14]. In Germany, officials at slaughter can use a three-or four-point scoring system to evaluate FPD in broilers [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation